Does Dynamic Non-Linear Relationship Drive Corporate Social Responsibility Disclosure and Financial Performance? - Edjoukou, Akadje Jean Roland; Edjoukou, Yessoh Gaudens Thecle; Wilson, Jonela Carmada Marisa; Bah, Monhesea Obrey Patrick (Journal of Contemporary Research in Social Sciences, 2022)
The aim of this paper is to generate an empirical estimation of the relationship between Corporate Social Responsibility Disclosure and Financial Performance by exploring the possibility of the existence of a non-linear relationship driving these two variables. Using a strongly balanced panel data with 2580 observations from 215 African listed firms over 12 years (2005-2016), the study investigated the short-run impact of CSRD through the Arellano-Bover /Blundell-Bond technique and the long-run effect via the Delta Method based on non-linear combinations of parameters estimated. The results indicate that in the short run, CSRD affects positively ROA while a negative significant relationship between the three-lagged measure of CSRD and ROA is also revealed. The results present the insignificance of the impact of CSRD on the other firm performances variables namely ROE, ROS. In the long run, CSRD is positively linked to all of the responses variables except ROE. Thus, the findings show that CSR practices do not generate benefit immediately. CSR effort positively affects firm financial performance in the following years after implementing it. Therefore, Managers should be aware that social practices should constitute an integrant part of overall firm strategy in order to achieve great profit.